Thyroid nodules: Global, economic, and personal burdens - Uppal, Nishant; Collins, Reagan; James, Benjamin (Frontiers in Endocrinology, 2023)
Thyroid nodules have garnered attention due to changes in population surveillance systems and rising concerns about the associated financial burden on healthcare systems, payers, and patients. In this review, we find that prevalence rates vary widely based on method of detection and may particularly pronounced in asymptomatic patients undergoing routine screening. Incidence rates may be rising in lower-income and middle-income countries and may be declining in higher-income countries. Despite high incidence rates, survival rates continue to be as high as 97% for papillary thyroid cancer. Over the last few decades, thyroid nodule workup and management has grown more sophisticated with the advent of fine-needle aspiration biopsy, specialized biomarkers, and molecular testing. However, gaps remain in risk stratification that can lead to substantial costs of care. Certain molecular tests, such as the Afirma Gene Sequencing Classifier can lead to a cost per diagnosis of $17,873 while achieving only mild decreases in diagnostic lobectomies for patients (11.6% to 9.7% in one study). Out-of-pocket costs associated with thyroid nodule management continue to drive significant financial toxicity for patients, especially for individuals with thyroid cancer. Recent studies suggest that such toxicity can lead to adverse financial outcomes, such as foreclosure and bankruptcy. Additional cost-effectiveness analyses may be needed to improve existing thyroid nodule management systems and new clinical tools may be needed to avoid unnecessary workup and management.